Compliance of Distribution System Reactive Flows with Transmission System Requirements - Pediaditis, Panagiotis; Sirviö, Katja; Ziras, Charalampos; Kauhaniemi, Kimmo; Laaksonen, Hannu; Hatziargyriou, Nikos (MDPI, 2021)
Transmission system operators (TSOs) often set requirements to distribution system operators (DSOs) regarding the exchange of reactive power on the interface between the two parts of the system they operate, typically High Voltage and Medium Voltage. The presence of increasing amounts of Distributed Energy Resources (DERs) at the distribution networks complicates the problem, but provides control opportunities in order to keep the exchange within the prescribed limits. Typical DER control methods, such as constant cosϕ or Q/V functions, cannot adequately address these limits, while power electronics interfaced DERs provide to DSOs reactive power control capabilities for complying more effectively with TSO requirements. This paper proposes an optimisation method to provide power set-points to DERs in order to control the hourly reactive power exchanges with the transmission network. The method is tested via simulations using real data from the distribution substation at the Sundom Smart Grid, in Finland, using the operating guidelines imposed by the Finnish TSO. Results show the advantages of the proposed method compared to traditional methods for reactive power compensation from DERs. The application of more advanced Model Predictive Control techniques is further explored.
Keywords: grid code compliance; DER; reactive power control; optimisation; fi=Sähkötekniikka|en=Electrical Engineering|